Evaluation of community behavior regarding the risk of plastic micro-pollution on the environment health - D. Utari; N.I. Hawa; G. Fizumli; H. Agustina (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Plastic pollution is increasing globally along with the growing consumption patterns of the global community, leading to practicality (social behavior). The primary contributors to pollution are single-use plastic (SUP) items and inadequate waste management techniques. This research attempts to examine local communities’ determinants and behavioral patterns regarding plastic waste management.METHODS: This cross-sectional analytical study includes 195 respondents and conducted at Antang Lake, Makassar. The social sciences statistical package version 26 was used to perform chi-square tests and multiple regression analysis to examine the main elements influencing individual behavior toward plastic waste management. A survey instrument was provided to participants for data collection.FINDINGS: The chi-square test results show that the knowledge variable has a statistically significant relationship with plastic waste management behavior at home, with a test statistical value of 0.002. Respondents with limited knowledge are 2.603 times more likely to have poor household plastic waste management behavior than those with substantial knowledge. The knowledge variable is also significantly related to household plastic waste management behavior simultaneously with a statistical test value of 0.000, showing a strong relationship. This variable influences 11.8 percent of the behavior in question. Attitude and action variables do not have a significant relationship partially or simultaneously with household plastic waste management behavior.CONCLUSION: Increased plastic consumption has led to microplastic pollution, environmental damage, and deteriorating health conditions. Thus, intervention is required to improve optimal waste management behavior in the community. Increasing awareness about environmental management and educating the public on the impact of microplastics on family health can contribute to enhanced knowledge awareness. This research aims encourage greater awareness of environmental condition to minimize toxicity resulting from the negative impacts of plastic waste.